Association analysis of risk genes identified by SCHEMA with schizophrenia in the Chinese Han population. (14th September 2022) - Guo, Aiguo; Lun, Peng; Chen, Jianhua; Li, Qinghua; Chang, Kaihui; Li, Teng; Pan, Dun; Zhang, Jinmai; Zhou, Juan; Wang, Ke; Zhang, Qian; Yang, Qiangzhen; et al.
Abstract : Background: Schizophrenia is a chronic brain disorder. Previously, the Schizophrenia Exome Sequencing Meta-analysis consortium identified 10 highest risk genes related to schizophrenia. This study aimed to analyze the relationship between the 10 highest risk genes identified by the SCHEMA and schizophrenia in a Chinese population. Methods: A total of 225 variants in 10 genes were screened in a Chinese population of 6836 using a customized array. All variants were annotated through the Variant Effect Predictor tool, and the functional impacts of missense variants were assessed based on sorting intolerant from tolerant and PolyPhen-2 scores. The SHEsisPlus tool was used to analyze the association between risk genes and schizophrenia at the locus and gene levels. Results: At the locus level, no missense variants significantly related to schizophrenia were found, but we detected three missense variants that appeared only in cases, including TRIO p . Arg1185Gln, RB1CC1 p . Arg1514Cys, and HERC1 p . Val4517Leu. At the gene level, five genes ( TRIO, RB1CC1, HERC1, GRIN2A, and CACAN1G ) with more than one variant analyzed were kept for the gene-level association analysis. Only the association between RB1CC1 and schizophrenia reached a significant level (OR = 1.634; 95% CI, 1.062–2.516; P = 0.025). Conclusion: In this study, we determined that RB1CC1 might be a risk gene for schizophrenia in the Chinese population. Our results provide new evidence for recognizing the correlation of these risk genes with the Chinese schizophrenia population.